2005
DOI: 10.1159/000088704
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Bacterial Overgrowth in Symptomatic Older People: Can It Be Diagnosed Earlier?

Abstract: Background/Objectives: In older people, small bowel bacterial overgrowth syndrome may be a common, but under-diagnosed, cause of diarrhoea and nutrient malabsorption. We aim to determine which clinical features and baseline laboratory investigations indicate a high likelihood of small bowel bacterial overgrowth as defined by a positive glucose breath test. Methods: A retrospective analysis of records for all patients referred for glucose breath test over a 6-year period to a teaching hospital. Results: Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 55 publications
(35 reference statements)
1
40
4
Order By: Relevance
“…A predisposing anatomical abnormality, as the blind loop of Billroth II gastrojejunostomy, altered intestinal peristalsis, or hypochlorhydria induced surgically or pharmacologically by the use of PPI, can give rise to small intestinal overgrowth of bacteria [29,30]. SBBO has been recognized as an important cause of occult malabsorption in the elderly [31].…”
Section: Discussionmentioning
confidence: 99%
“…A predisposing anatomical abnormality, as the blind loop of Billroth II gastrojejunostomy, altered intestinal peristalsis, or hypochlorhydria induced surgically or pharmacologically by the use of PPI, can give rise to small intestinal overgrowth of bacteria [29,30]. SBBO has been recognized as an important cause of occult malabsorption in the elderly [31].…”
Section: Discussionmentioning
confidence: 99%
“…He had however had no further falls. Although bacterial overgrowth can also cause low B 12 post hemicolectomy, the patient denied any diarrhoea and there was no biochemical evidence of malabsorption [5]. The delay in manifestation of B₁₂ deficiency is due to the large amounts of B₁₂ stored in the liver and therefore any reduction in vitamin B₁₂ for whatever mechanism may take five to ten years to manifest clinically.…”
mentioning
confidence: 88%
“…30 Moreover, although it is thought that PPIs have a minor effect on altering the intestinal bacterial microbiota and observational studies have suggested that PPIs may or may not increase risk of enteric infections, these drugs can cause bacterial overgrowth in the small bowel and consequently the diarrheal disease defined as small intestinal bacterial overgrowth syndrome, sometimes mistakenly diagnosed as irritable bowel syndrome. 31,32 PPIs not only increase intestinal bacterial colonization but also accelerate intestinal transit.…”
Section: Gastrointestinal Infectionsmentioning
confidence: 99%